Pruning and training systems for modern olive growing - Gucci, Riccardo, 1959-; Cantini, Claudio (Australia: Csiro Publishing, 2004)
Olive growing is expanding rapidly in many countries around the world in which olives have not previously been widely cultivated. Pruning olive trees is quite different from pruning other fruit trees of the temperate zone, because of their biological peculiarities. Errors in pruning may result in yield losses or higher cultivation costs. Pruning also determines the training system which, in turn, is one of the major factors for successful tree performance and orchard profitability. Pruning and Training Systems for Modern Olive Growing summarises the information available on current pruning techniques and training systems. It specifically addresses the problems faced by growers, professionals and students who are new to olive growing and provides information previously not available in English. The fundamental aim of this book is to explain the basic concepts at a practical level. It will allow the reader, whether experienced horticulturalist or beginner, to develop his or her own skills and pruning strategy.
-- Contents -- Preface -- Acknowledgements -- 1 Introduction -- Show Level 2 Basic principles for pruning woody crops -- Show Level 3 Physiological background for pruning olive trees -- Show Level 4 Pruning olive trees -- Show Level 5 Pruning young trees -- Show Level 6 Pruning mature trees -- Show Level 7 Criteria for selecting the training system -- Show Level 8 Description of modern training systems -- Show Level 9 Comparisons of training systems -- 10 Conclusions -- References -- Index
Includes bibliographical references and index.
Keywords: Olive -- Australia; Olive -- Pruning; Olive -- Training